Measurement of the ratios of branching fractions ℛ⁡(𝐷*) and ℛ⁡(𝐷0) - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; Leverington, Blake; et al. (Physical review letters, 2023)
The ratios of branching fractions ℛ⁡(𝐷*)≡ℬ⁡(¯𝐵→𝐷*⁢𝜏−⁢¯𝜈𝜏)/ℬ⁡(¯𝐵→𝐷*⁢𝜇−⁢¯𝜈𝜇) and ℛ⁡(𝐷0)≡ℬ⁡(𝐵−→𝐷0⁢𝜏−⁢¯𝜈𝜏)/ℬ⁡(𝐵−→𝐷0⁢𝜇−⁢¯𝜈𝜇) are measured, assuming isospin symmetry, using a sample of proton-proton collision data corresponding to 3.0  fb−1 of integrated luminosity recorded by the LHCb experiment during 2011 and 2012. The tau lepton is identified in the decay mode 𝜏−→𝜇−⁢𝜈𝜏⁢¯𝜈𝜇. The measured values are ℛ⁡(𝐷*)=0.281±0.018±0.024 and ℛ⁡(𝐷0)=0.441±0.060±0.066, where the first uncertainty is statistical and the second is systematic. The correlation between these measurements is 𝜌=−0.43. The results are consistent with the current average of these quantities and are at a combined 1.9 standard deviations from the predictions based on lepton flavor universality in the standard model.
*LHCb Collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, J. Marks, M.P. Morgenthaler, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola [und 1047 weitere Personen]
Im Titel sind das Asterix-Zeichen sowie die Zahl 0 hochgestellt
Gesehen am 03.07.2024